Dispersibility of Multiwall Carbon Nanotube in a Polyanionic Surfactant Based on UV-Vis Analysis - Yuyun Irmawati; Deni Shidqi Khaerudini; Indriyati Indriyati; Mardiyati Mardiyati; Rike Yudianti (Indonesian Journal of Chemistry, 2020)
The degree of carbon nanotube (CNT) dispersion in an ink solution plays a critical role in the performance of CNT based devices. This is a challenging task in the CNT utilization due to strong van der Waals interaction affecting the CNT bundles. A good dispersion degree can be achieved, for instance, by lowering the van der Waals interaction with the strategy of non-covalent interaction between polyanionic surfactant and the CNT surface. Herein, a simple and quick technique to disperse multiwall CNT (MWCNT) by using a polyanionic dispersant, carboxymethyl cellulose (CMC), is reported. The dispersion degree of MWCNT in aqueous solution during the sonication process was studied using UV-Vis analysis. Transmission electron microscope (TEM) was also applied to further investigate the interaction between CMC and MWCNT. The result shows that the maximum dispersion of MWCNT was achieved with a maximum absorbance in the UV-Vis spectra. Higher CMC concentration resulted in a higher viscosity of the solution, thus it increased the sonication duration in obtaining the maximum dispersion. By varying the MWCNT concentration at a constant CMC concentration of 0.25 wt.%, a homogenous MWCNT dispersion was obtained up to 0.2 wt.%. The encapsulation of a thin CMC layer on the MWCNT surface with a thickness of 1.5–3 nm was evidenced by TEM micrograph analysis.